Pharmacology and clinical trials of reversibly-binding P2Y12 inhibitors - Storey, Robert F. (Thrombosis and Haemostasis, 2011)
The important role of the P2Y12 receptor in amplification of platelet activation and associated responses and the limitations associated with clopidogrel therapy have led to the development of novel inhibitors of this receptor. Three reversibly-binding P2Y12 inhibitors are in phase 3 development, ticagrelor, cangrelor and elinogrel. The pharmacology and clinical trial data for each of these inhibitors are discussed and compared with relevant data for the thienopyridines clopidogrel and prasugrel.
Keywords: ADP receptors; antiplatelet agents; arterial thrombosis; platelet pharmacology; antiplatelet drugs